The Output Costs of Hard and Soft Sovereign Default - Christoph Trebesch; Michael Zabel (Center for Economic Studies and ifo Institute (CESifo), 2016)
How costly are sovereign debt crises? In this paper we study output losses during sovereign default and debt renegotiation episodes since 1980. In contrast to previous work, we account for the severity of default and not only for its occurrence. Specifically, we distinguish between “hard” and “soft” defaults, using new data on debtor payment and negotiation behavior and on the size of haircuts towards private external creditors. We show that hard defaults are associated with a much steeper drop in GDP, of up to ten percent, compared to soft defaults, and address concerns of reverse causality and omitted variable bias. The results question the standard assumption that defaults trigger fixed and lump-sum costs. Instead, our findings are consistent with models assuming proportional output costs of default.
Keywords: F34; F41; H63; G01; 330; sovereign debt crises; debt restructuring; economic growth; reputation